An infrared earth horizon sensor for a LEO satellite - Van Rensburg, Helgard Marais (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2008.